Government Spending and Economic Growth in Cameroon - Siefu, Donald Djatcho; Njocke, Martin; Yah, Neba Cletus (European Scientific Journal, ESJ, 2018)
Today, the role of government spending which is considered as the main instrument in the promotion of economic development is seen in the public investment budget (PIB). This study analyzes the role of the public investment spending in the economic growth of Cameroon. Specifically, it brings out the effect of Public and Private Investment on GDP growth in Cameroon. The role of the PIB as an instigator of economic growth should be clarified in order to justify government investment expenditure. Many studies have analysed the relationship between government spending and economic growth but the analysis of the composition of government spending and induced economic growth is an aspect of economic analysis which deserves more interest. This study analysis the effect of government investment spending on economic growth in Cameroon going from the components of the GDP5 and using VAR (Vector Auto Regressive) model. Our results show the intervals in which the various components of government spending have an effect on economic growth in Cameroon. We find that the lagged GDP and government investments have a positive effect on growth whereas private investments affect it negatively.